CP-188 Intra-abdominal infections in digestive surgery wards: Is empiric antibiotic treatment in accordance with local microbiological ecology?. (14th February 2016) - Gougeon, M; Lafaurie, M; Vancassel, M; Segonds, C; Cestac, P; Cool, C; Duhalde, V
Abstract : Background: In 2014, new expert recommendations on treatment of intra-abdominal infections (IAI) were published. They highlighted the importance of starting empiric antibiotic therapy considering the local microbiological resistance profile and the community acquired or nosocomial character of the infection. Purpose: The goal was to analyse antibiotic consumption in digestive surgery wards (DSW) with pathogen microorganism found in the intra-abdominal fluid (IAF), to propose a new empiric antibiotic treatment of IAI according to the recommendations. Material and methods: Bacteriological and mycological analyses have been performed on all IAF samples of patients hospitalised in DSW in 2014. Antibiotic consumption was analysed between 2013 and June 2015. The results have been expressed in daily defined dose (70 kg adult usual daily drug posology for its principal indication) for 1000 hospitalisation days (DDD/1000HD). Results: For 77 IAF samples analysed, 41 (53%) were positive. For 77 bacterial strains, 37 (48%) were enterobacteria, 14 (18%) anaerobic bacteria, 11 (14%) enterococcus, 6 (7.8%) streptococcus, 4 (5%) candida, 3 (4%) Staphylococcus aureus and 2 (2.6%) Pseudomonas aeruginosa . Two E coli were third generation cephalosporin (3GC) resistant. 11 enterobacteria were resistant to nalidixic acid. Two staphylococcus patients were methicillin sensible. Between 2013 and 2015, cephalosporin and metronidazole prescriptions were stable, 66 vs. 61 DDD/1000HD and 112 vs. 115 DDD/1000HD, respectively. Carbapenem consumptions increased by 42% (50 vs. 71 DDD/1000HD), fluoroquinolone prescriptions decreased by 59% (86 vs. 35 DDD/1000HD) and antifungal prescriptions decreased by 33% (61 vs. 41 DDJ/1000HD). Echinocandin use decreased between 2014 and 2015 by 39% (18 vs. 11 DDD/1000HD). Conclusion: Empiric antibiotic treatment of community acquired IAP without serious symptoms was ceftriaxone with metronidazole, respecting recommendation thanks to the small proportion of resistant E coli to 3GC. The increase in carbapenem prescriptions concerned meropenem, which is recommended in nosocomial IAP with the risk factor of multidrug resistant bacteria. To preserve this antibiotic class, it is important to evaluate treatment at initiation and to reassess when the bacteria are identified. Since an infectious multidisciplinary meeting was set up in 2014, antifungal prescriptions are restricted to patients with serious symptoms. This study highlights the imperative need to review antibiotic strategy according to local ecology and guidelines. No conflict of interest.